Octave Bias in Pitch Perception: The Influence of Pitch Height on Pitch Class Identification. (September 2016) - Prpic, Valter; Murgia, Mauro; De Tommaso, Matteo; Boschetti, Giulia; Galmonte, Alessandra; Agostini, Tiziano
Pitch height and pitch class are different, but strictly related, percepts of music tones. To investigate the influence of pitch height in a pitch class identification task, we systematically analyzed the errors—in terms of direction and amount—committed by a group of musicians. The aim of our study was to verify the existence of constant errors in the identification of pitch classes across consecutive octaves. Stimuli were single piano tones from the C major scale executed in two consecutive octaves. Participants showed different response patterns in the two octaves. The direction of errors revealed a constant tendency to underestimate pitch classes in the lowest octave and to overestimate pitch classes in the highest octave. Thus, pitch height showed to influence pitch class identification. We called this bias "pitch class polarization", since the same pitch class was judged to be respectively lower and higher, depending on relatively low or high pitch height.